Creation of national regions as a means of ensuring rights and freedoms of Russian Germans: on the example of Azovsky Nemetsky (German) National District - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
Maintaining political stability and unity of the territory of the state is an important task for any government. It becomes especially relevant in cases where different territories of the state have ethnically different populations. Areas with mixed populations, especially those driven by migration, are potential areas of stress. Reasonable implementation of the rights and freedoms of citizens in economic and cultural terms, freedom of movement, is a guarantee of stable development or at least peaceful migration. An analysis of the history of the creation of German national regions in the USSR shows a picture of the gradual assimilation of the German population or its migration outside the country. The article discusses the creation of a Azovsky Nemetsky (German) National District to ensure economic and cultural rights. The work is carried out on the basis of multifaceted sources. As a result of the fulfillment of the goal of the study — the reconstruction of the history of the region’s reconstruction against the background of the development of the German national movement and the influence of its international obligations on the country’s leadership, the following conclusions can be drawn. The creation of the Azovsky Nemetsky (German) National District is culturally, economically and politically expedient. Of interest there are also the conclusions about the possibilities within the framework of the Azovsky Nemetsky (German) National District to resolve the problems of emigration and migration, as well as the issues of raising the standard of living of the population.